Exploring the Influence of Supplier Relationship Quality on South African Municipalities’ Service Delivery Performance - Kasai, Stanford; Chiliya, Norman (Indian Journal of Finance, 2022)
Most South African municipalities are yet to perform at the desired level. Service delivery protests have been a permanent feature in the South African media for years. Apprehending the factors influencing relationship quality may help municipalities enhance their performance and reduce service delivery problems. The study adopted a quantitative approach within the South African municipality setting. The respondents were sampled using stratified random sampling and snowball sampling. Data were collected from 205 respondents using a structured 5-point Likert scale questionnaire. The data were coded and analyzed using descriptive statistics, SPSS, and AMOS statistical software. The main finding was that relationship quality influenced service delivery performance from the management’s perspective. The composite relationship quality variables (cooperation, trust, commitment, and satisfaction) significantly influenced the relationship quality. The implication is that the quality of the relational interactions between the municipalities and their suppliers significantly impacted the quality-of-service delivery performance.